2018
DOI: 10.3390/cancers10010025
|View full text |Cite
|
Sign up to set email alerts
|

Localization Microscopy Analyses of MRE11 Clusters in 3D-Conserved Cell Nuclei of Different Cell Lines

Abstract: In radiation biophysics, it is a subject of nowadays research to investigate DNA strand break repair in detail after damage induction by ionizing radiation. It is a subject of debate as to what makes up the cell’s decision to use a certain repair pathway and how the repair machinery recruited in repair foci is spatially and temporarily organized. Single-molecule localization microscopy (SMLM) allows super-resolution analysis by precise localization of single fluorescent molecule tags, resulting in nuclear stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 62 publications
4
62
0
Order By: Relevance
“…It has been shown that such foci can be separated into functionally relevant sub-foci or clusters of about the same size independent from the dose applied [23,28,29]. This has also been found for the cell nuclei analyzed here (see Figure S2).…”
Section: Resultssupporting
confidence: 78%
“…It has been shown that such foci can be separated into functionally relevant sub-foci or clusters of about the same size independent from the dose applied [23,28,29]. This has also been found for the cell nuclei analyzed here (see Figure S2).…”
Section: Resultssupporting
confidence: 78%
“…After data analysis, artificial "pointillist" super-resolution images can be generated, in which the results of data analysis can additionally be encoded [40]. SMLM was applied to investigate the irradiation effects on chromatin nano-architecture [28,36,37] and protein organization at the nano scale [41][42][43], revealing systematic dose- [40,44] and locus-dependent [45] chromatin conformation changes. For multi-color localization microscopy of DNA damage markers along alpha tracks, we here applied molecular labelling with specific antibodies against γ-H2AX, MRE11, and 53BP1 in alpha-traversed cell nuclei and studied their distribution within γ-H2AX foci domains (super-foci) that demarcate the particle track.…”
Section: Introductionmentioning
confidence: 99%
“…These steps allow the efficient recruitment of the repair factors to the damaged DNA regions and implicate in the choice between the DNA repair pathways. For examining the DSB-induced chromatin changes, confocal microscopy-based techniques are used in most of the studies, although in the last few years high-throughput chromosome conformation capture technique (4C) and single cell microscopy were utilized to gain detailed insights about the protein interactions and cascades involved in the different repair pathways 31,5357 . A more detailed overview has raised more questions, which could be answered only at a single-cell level: how the different DNA repair pathways are chosen and how individual repair proteins are regulated to access the DNA repair site.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitation of the technique is that it shows the average of a given focus by combining the data obtained from a large population of cells. Recent applications of electron-microscopy and super-resolution light microscopy 24,30,31,5557 have demonstrated that it is feasible to study single molecular arrangements within a repair focus. By improving the resolution of microscopy and data evaluation of structures in meso-and nano-scale level, the searching for the best-suited analysis parameters and potentially useful classification criteria of repair foci and damaged chromatin sites have become to be important.…”
Section: Discussionmentioning
confidence: 99%